2019
DOI: 10.1016/j.jnucmat.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced amorphization in the zirconium suboxide on Zr-0.5Nb alloys

Abstract: We report for the first time the observation of irradiation-induced amorphization of the zirconium suboxide formed during aqueous corrosion of Zr-0.5Nb alloys. High-resolution transmission electron microscopy results reveal amorphization of the hexagonal-ZrO suboxide under heavy ion irradiation at cryogenic temperatures. This irradiation-induced amorphization behaviour is discussed in relation to the arrangement of oxygen interstitials and the formation of stable superlattices. The sensitivity of the suboxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This ZrO was also predicted from an ab-initio study to have a structure similar to hexagonal ω-Zr (space group, P6/mmm, a=5.02-5.03A, c=3-3.11A [21,22]), with a high content of oxygen [19,20]. The thickness of h-ZrO suboxide layers has been observed to correlate well to the instantaneous oxidation rate [23], and our recent in-situ irradiation results have revealed that the h-ZrO suboxide is particularly susceptible to radiation damage [24], which may be a contributing factor to help explain the acceleration of corrosion rate of zirconium alloys observed in-service [25]. However, the mechanism by which the h-ZrO forms has not yet been explored.…”
Section: Introductionmentioning
confidence: 69%
“…This ZrO was also predicted from an ab-initio study to have a structure similar to hexagonal ω-Zr (space group, P6/mmm, a=5.02-5.03A, c=3-3.11A [21,22]), with a high content of oxygen [19,20]. The thickness of h-ZrO suboxide layers has been observed to correlate well to the instantaneous oxidation rate [23], and our recent in-situ irradiation results have revealed that the h-ZrO suboxide is particularly susceptible to radiation damage [24], which may be a contributing factor to help explain the acceleration of corrosion rate of zirconium alloys observed in-service [25]. However, the mechanism by which the h-ZrO forms has not yet been explored.…”
Section: Introductionmentioning
confidence: 69%
“…Cracks and pores [6], interconnected porosity [18,19] and oxide grain boundaries [20,21] have all been suggested as preferential pathways for hydrogenic, as well as oxidising, species to reach the metal surface. Recent studies have shown that the oxide film has a complicated microstructure containing several different types of nano-porosity [22,23], and in addition to the bulk ZrO2 oxide (mostly monoclinic and some tetragonal [24] ), a metastable ZrO suboxide may form at the metal-oxide interface [25][26][27][28]. Thus there may be several possible pathways for hydrogen ingress, and different specific nanostructures through which the hydrogenic species must pass to reach the underlying Zr metal.…”
Section: Introductionmentioning
confidence: 99%
“…The physical depth resolution can thus be estimated by the visibility of Kikuchi bands in carefully selected regions with overlapping phases, and the effective resolution estimated depending on the capability of the software to deconvolute the predominant orientation from the overlapping Kikuchi patterns. These same Zr-Nb alloys are being studied as corrosion-resistant nuclear fuel cladding materials [2], and the oxides formed by aqueous corrosion have a characteristic nanoscale grain structure [23,24] which can also be studied by TKD analysis.…”
Section: Methodsmentioning
confidence: 99%